THE INFLUENCE OF PAST EXPERIENCE OF LEARNING IN HIGHER EDUCATION AND THE NOVICE TEACHER'S EXPERIENCE ON THEIR PROFESSIONAL ACTIVITIES - Yusmanita; Sukri Adani (Yayasan Nusantara Hasana Berdikari, 2024)
This research explores the transition of novice teachers from higher education to professional practice, focusing on the impact of college learning experiences and early teaching experiences on their professional readiness, teaching effectiveness, and the development of pedagogical skills and professional identity. Through a qualitative case study approach involving 15 novice teachers, the study examines how theoretical foundations acquired in higher education contribute to teaching preparedness, while also identifying the challenges posed by the gap between theory and classroom practice. The findings reveal that while higher education provides a solid theoretical framework, novice teachers often feel underprepared for the complexities of real-world teaching. Early teaching experiences, such as practicum and internships, are crucial in bridging this gap, allowing teachers to apply theoretical knowledge in practical contexts, develop classroom management strategies, and adapt to diverse student needs. The study underscores the importance of continuous support from mentors and collaboration with colleagues in fostering professional growth and confidence among novice teachers. The research concludes that to enhance the effectiveness of teacher education programs, there is a need to integrate more practical experiences with theoretical learning and to create a collaborative, supportive learning environment. This approach would better prepare novice teachers for the challenges of the classroom and contribute to their long-term professional success.